Evaluasi Implementasi Kebijakan Disiplin Pegawai Negeri Sipil Daerah - Rusliandy Rusliandy (Ideas Publishing, 2022)
Tujuan penelitian ini adalah mengevaluasi implimentasi kebijakan disiplin PNS daerah yang meliputi evaluasi summative, evaluasi proses, dan evaluasi konsekuensi. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan library research. Hasil penelitian ini menyebutkan: (1) evaluasi summative menunjukan empat regulasi yang mengatur disiplin PNS sejak tahun 1952, (2) evaluasi proses menunjukkan variasi implementasi yang disebabkan lima hal, dan (3) evaluasi konsekuensi. Strategi perbaikan meliputi perbaikan kebijakan disiplin melalui sanksi bagi kepala, perubahan mekanisme pemanggilan, pemeriksaan atasan dan dan perbaikan dalam implementasi yang mencakup keteladanan, pemahaman peraturan, dan pembinaan disiplin. The purpose of this study was to evaluate the implementation of regional civil servant discipline policies, including summative evaluation, process evaluation, and consequence evaluation. The research method used is a qualitative approach with library research. The results of this study indicate that: (a) The summative evaluation shows that four regulations have governed civil servant discipline since 1952, (b) The process evaluation shows that there are variations in implementation due to the commitment of regional heads and direct superiors, the capacity of direct superiors, exemplary to officials, weakness evidence, as well as variations regulated in-laws and regulations, (c) Evaluation of consequences. First, the improvement strategies are the improvement of disciplinary policies through the need for sanctions for regional heads who do not impose disciplinary penalties, changes in the arrangement of summons, and inspection mechanisms by direct superiors. Second, improvements in implementation, namely the need for exemplary from the leadership of the agency, the need for socialization to all superiors about a comprehensive understanding of disciplinary regulations, and the importance of the stages of disciplinary development for civil servants who violate discipline.